Climate change and poverty of small-scale agricultural producers: towards a future research agenda – supplementary data - Campbell, Bruce M.; Chang, Yuling; Smit, Wiebe; Vertegaal, Doris M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Campbell et al. (submitted) undertook a review of the climate-poverty literature from 2002-2018 with a focus on small-scale agricultural producers. Peer-reviewed literature searches through the Web of Science Platform was conducted and yielded close to 400 journal articles (see the full list below). To identify articles, the search terms used are shown in Table 1, but this was followed by manual checking that articles covered all three elements: climate change, agriculture/food security and poverty. The full versions of each of the selected papers were then searched for specific terms in order to understand the focus of the literature.